The influence of different footwear on 3-D kinematics and muscle activation during the barbell back squat in males - Sinclair, J.; McCarthy, D.; Bentley, I.; Hurst, H. T.; Atkins, S. (European Journal of Sport Science, 2015)
The barbell back squat is commonly used by athletes participating in resistance training. The barbell squat is typically performed using standard athletic shoes, or specially designed weightlifting footwear, although there are now a large number of athletes who prefer to squat barefoot or in barefoot-inspired footwear. This study aimed to determine how these footwear influence 3-D kinematics and muscle activation potentials during the barbell back squat. Fourteen experienced male participants completed squats at 70% 1 rep max in each footwear condition. 3-D kinematics from the torso, hip, knee and ankle were measured using an eight-camera motion analysis system. In addition, electromyographical (EMG) measurements were obtained from the rectus femoris, tibialis anterior, gastrocnemius, erector spinae and biceps femoris muscles. EMG parameters and joint kinematics were compared between footwear using repeated-measures analyses of variance. Participants were also asked to subjectively rate which footwear they preferred when performing their squat lifts; this was examined a chi-squared test. The kinematic analysis indicated that, in comparison to barefoot the running shoe was associated with increased squat depth, knee flexion and rectus femoris activation. The chi-squared test was significant and showed that participants preferred to squat barefoot. This study supports anecdotal evidence of athletes who prefer to train barefoot or in barefoot-inspired footwear although no biomechanical evidence was found to support this notion.